Hippo/YAP signaling’s multifaceted crosstalk in cancer - Jie Zhang; Haipeng Wu; Haipeng Wu; Xinxin Ren; Zhuoshi Chen; Siyu Ye; Shuchang Chen; Jie Fang; Qirou Wu; Tiejun Zhao; Tiejun Zhao (Frontiers in Cell and Developmental Biology)
The Hippo/yes-associated protein (YAP) signaling is an evolutionarily conserved regulator in organ size control, which plays pivotal roles in cell proliferation, differentiation, apoptosis, and tissue regeneration. In cancer, dysregulation of Hippo/YAP signaling is typically recognized as one of the crucial drivers in tumorigenesis. However, beyond its canonical transcriptional targets, Hippo/YAP signaling engages in extensive crosstalk with multiple pathways to form an intricate regulatory network, thereby giving rise to its content-dependent influence on tumor initiation, progression and metastasis. This review focuses on the molecular mechanisms underlying the interplay between Hippo/YAP and pivotal signaling pathways such as nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), wingless-type (Wnt)/β-catenin signaling pathway, transforming growth factor-beta (TGF-β), Hedgehog, Notch and other signaling pathways, as well as their implications in cancer biology. Ultimately, exploiting these mechanisms may represent promising therapeutic strategies for cancer.